Análise do padrão de ativação muscular de indivíduos hemiparéticos pós-AVC em marcha assistida por andador robótico - Loterio, Flávia Aparecida (2015)
Stroke is a leading cause of damages in the neuromuscular system. Robotic devices have been widely developed and studied in order to be used in gait assistance and gait training during the rehabilitation. The goal of this work is to evaluate the assisted gait by the AROW (Assistive Robotic Walker) in post stroke hemiparetic individuals through accelerometer signals and surface Electromyography (sEMG) analysis. The analyzed muscles are vastus medialis (VM), biceps femoris (BF), tibialis anterior (TA) and gastrocnemius medialis (GM). Furthermore, the evaluation methods GAS (Goal Attainment Scaling) and SUS (System Usability Scale) were used. Nine hemiparetic subjects participate of the experiments. The gait speed was decreased using the walker and, consequently, there were some changes in the duration of gait phases, for instance longer of support phase (p = 0.0174). The muscle activation pattern for the analyzed group did not show statistically significant difference (onset VM: p= 0.4999; offset VM: p= 0.5647; onset BF: p= 0.1186; offset BF: p= 0.7823; onset TA: p= 0.5833; offset TA: p= 0.8393; onset GM: p= 0.6077; offset GM: p= 0.1429).. However, assessing the muscle activation pattern individually, some benefic changes can be noted, for example, the reduced co-activation between tibialis anterior and gastrocnemius medial. The results of evaluations through GAS (54.8) and SUS (81.4) about the use of the AROW showed good acceptance among users, and the desired results during the use of the walker were achieved. The fast adaptation, easiness of use and feeling of safety when using the device are positive points that were obtained using the AROW.